Integrated Analysis of Angiogenesis Related lncRNA-miRNA-mRNA in Patients With Coronary Chronic Total Occlusion Disease - Gao, Wei; Zhang, Jianhui; Wu, Runda; Yuan, Jie; Ge, Junbo (Frontiers in Genetics, 2022)
Background: Coronary chronic total occlusion (CTO) disease is common and its specific characteristic is collateral formation. The Integrated analysis of angiogenesis related lncRNA-miRNA-mRNA network remains unclear and might provide target for future studies. Materials and Methods: A total of 5 coronary artery disease (control group) and 5 CTO (CTO group) patients were selected for deep RNA and miRNA sequencing. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were then performed. The expression of a 14q32 miRNA gene cluster, including miRNA-494, miRNA-495 and miRNA-329, were selected to be determined in another larger patient cohort. Results: A total of 871 lncRNAs, 1080 mRNAs, 138 circRNAs and 56 miRNAs were determined as differentially expressed (DE) in CTO patients compared with control patients. GO and KEGG analyses revealed that the top terms included MAPK signaling pathway, HIF-1 signaling pathway, EGFR tyrosine kinase inhibitor resistance, embryonic organ development, wound healing, MAPK signaling pathway and JAK-STAT signaling pathway, which are related to angiogenesis. The expression of miRNA-494, miRNA-495 and miRNA-329 were all significantly down-regulated in CTO patients and they were confirmed to be down-regulated in another cohort of 68 patients. These miRNAs were further found to be down regulated in good collateral circulation group. Analysis of the lncRNA-miRNA495-mRNA network showed 3 DE lncRNA sponges (NONHSAG008675, NONHSAG020957 and NONHSAG010989), 4 DE lncRNA targets (NONHSAT079547.2, NONHSAT081776.2, NONHSAT148555.1 and NONHSAT150928.1) and 2 DE mRNA targets (RAD54L2 and ZC3H4) of miRNA495. Conclusion: This study revealed that the lncRNA-miRNA-mRNA network might play a critical role in angiogenesis in CTO patients.